2005
DOI: 10.1111/j.1365-2125.2005.02542.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a new testosterone transdermal delivery system, TDS®‐testosterone in healthy males

Abstract: Aims The Transdermal Delivery System (TDS®) is a liquid formulation that can be applied to the skin via a metered pump spray to deliver drug to the systemic circulation. The aims of this study were to assess the ability of the TDS® preparation to deliver testosterone systemically, and to characterize the pharmacokinetic profiles of the hormone in healthy males. Methods An open label, comparative, randomized placebo controlled study involving three treatments and three periods with a minimum of a 1 week washout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…These topical preparations include gels, topical aerosols, and spray systems that contain volatile solvent(s) such as ethanol and/or water which evaporates upon application leaving the active drug and chemical enhancer on the skin surface. It has been suggested that these delivery systems are more convenient and patient friendly in comparison to other delivery systems such as transdermal patches [8]. For example, the metered dose aerosol system for the systemic delivery of drugs such as testosterone, estradiol, and buspirone has been recently investigated [9].…”
Section: Introductionmentioning
confidence: 99%
“…These topical preparations include gels, topical aerosols, and spray systems that contain volatile solvent(s) such as ethanol and/or water which evaporates upon application leaving the active drug and chemical enhancer on the skin surface. It has been suggested that these delivery systems are more convenient and patient friendly in comparison to other delivery systems such as transdermal patches [8]. For example, the metered dose aerosol system for the systemic delivery of drugs such as testosterone, estradiol, and buspirone has been recently investigated [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chik et al reported on a liquid T formulation that can be applied to the skin via a metered pump spray [147]. Comparing the pharmacokinetics of this spray (T 50 mg per dose) with those of T gel 50 mg, the serum T concentrations in the first 12 h following administration were found to be bioequivalent to the T gel.…”
Section: Other Novel Approaches For Transdermal Testosterone Deliverymentioning
confidence: 94%
“…Comparing the pharmacokinetics of this spray (T 50 mg per dose) with those of T gel 50 mg, the serum T concentrations in the first 12 h following administration were found to be bioequivalent to the T gel. Another group is also working on the development of T transdermal sprays [147,148].…”
Section: Other Novel Approaches For Transdermal Testosterone Deliverymentioning
confidence: 99%
“…The 24 subjects had concomitant endocrine disorders (hypopituitarism (16), primary hypogonadism (5), hyperprolactinaemia (2), goitre (1) and hypothyroidism (1)). This resulted in concomitant medication for 22 subjects including thyroid hormones (14), glucocorticoids (12), somatropin or analogues (10) and prolactine inhibitors (8). Seven subjects affected by primary hypogonadism had FSH levels higher than the upper normal limit of 8 IU/L and the remaining 17 subjects suffering from secondary hypogonadism had FSH values lower than 8 IU/L except one hypopituitaric subject.…”
Section: Patient Populationmentioning
confidence: 95%